Assessing economic complexity with input-output based measures - Lopes, João Carlos (2010)
Economic complexity can be defined as the level of interdependence between the component parts of an economy. In input-output systems, intersectoral connectedness is a crucial feature of analysis, and there are many different methods for measuring it. Most of the measures, however, have drawbacks that prevent them from being used as a good indicator of economic complexity, because they were not explicitly made with this purpose in mind. In this paper, we present, discuss and compare empirically different indexes of economic complexity as intersectoral connectedness, using the interindustry tables of several OECD countries.